2011
DOI: 10.1128/jb.01109-10
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactis ZitR Is a Zinc-Responsive Repressor Active in the Presence of Low, Nontoxic Zinc Concentrations In Vivo

Abstract: In the family Streptococcaceae, the genes encoding zinc ABC uptake systems (called zit or adc) are regulated by a coencoded MarR family member (i.e., ZitR or AdcR), whereas in the great majority of bacteria, these genes are regulated by Zur, the Fur-like zinc-responsive repressor. We studied the zit operon from Lactococcus lactis and its regulation in response to Zn(II) in vivo. zit transcription is repressed by Zn(II) in a wide concentration range starting from nontoxic micromolar levels and is derepressed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…MarR proteins that respond to salicylate, urate, zinc, and a number of antibiotics have been studied (1,21,27,42). Also, MarR regulators for aromatic catabolic pathways that respond to m-chlorobenzoate, m-hydroxybenzoate, and p-hydroxybenzoate have been reported (5,32,45).…”
Section: Discussionmentioning
confidence: 99%
“…MarR proteins that respond to salicylate, urate, zinc, and a number of antibiotics have been studied (1,21,27,42). Also, MarR regulators for aromatic catabolic pathways that respond to m-chlorobenzoate, m-hydroxybenzoate, and p-hydroxybenzoate have been reported (5,32,45).…”
Section: Discussionmentioning
confidence: 99%
“…Purified ZitR is a dimer with up to two zinc ligands per monomer. It specifically binds two intact palindromic operator sites overlapping the Ϫ35 and Ϫ10 boxes of the zit promoter (75). ZitR requires Zn 2ϩ to bind DNA, and transcriptional analyses have shown that zitSQP expression is induced only at Zn 2ϩ concentrations below 100 nM, indicating that ZitR acts as a sensor of Zn 2ϩ scarcity (75).…”
Section: One-component Systemsmentioning
confidence: 99%
“…It specifically binds two intact palindromic operator sites overlapping the Ϫ35 and Ϫ10 boxes of the zit promoter (75). ZitR requires Zn 2ϩ to bind DNA, and transcriptional analyses have shown that zitSQP expression is induced only at Zn 2ϩ concentrations below 100 nM, indicating that ZitR acts as a sensor of Zn 2ϩ scarcity (75). S. pneumoniae encodes a homologous Zn 2ϩ uptake system (AdcABC) that is regulated by a ZitR homolog (AdcR) (76).…”
Section: One-component Systemsmentioning
confidence: 99%
“…First, AdcR (ZitR in L. lactis 25 ) has a unique effector in Zn(II). Additionally, the co-repression mechanism induced by metal binding to AdcR is unprecedented in MarR family transcriptional regulators.…”
mentioning
confidence: 99%